Identifikasi Miskonsepsi Penurunan Titik Beku dan Kenaikan Titik Didih pada Mahasiswa Pendidikan Kimia - Agung, Darius; Fauziah, Cindy; Salsabila, Hajidah (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
This study aims to identify misconceptions about colligative properties, especially freezing point depression and boiling point elevation, which occur in chemistry education students. The research was conducted by distributing an online survey, which contained open-ended essay questions, to several chemistry education classes at 3 state universities on the island of Java. The answers were then analyzed, and the results identified 12 misconceptions among the participants. This finding shows the need for a change in the way colligative material is delivered at the tertiary level.